2021
DOI: 10.1016/j.drugalcdep.2021.108590
|View full text |Cite
|
Sign up to set email alerts
|

Associations between vaping and Covid-19: Cross-sectional findings from the HEBECO study

Abstract: Aims To explore i) associations between vaping and self-reported diagnosed/suspected Covid-19; ii) changes in vaping since Covid-19 and factors associated with these changes; iii) whether Covid-19 motivated current or recent ex-vapers to quit. Methods Cross-sectional online survey of 2791 UK adults recruited 30/04/2020–14/06/2020. Participants self-reported data on sociodemographic characteristics, diagnosed/suspected Covid-19, vaping status, changes in vaping and motiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 37 publications
5
21
2
Order By: Relevance
“…These findings highlight the importance of continued public health messaging on smoking, especially as we emerge from the Covid-19 pandemic. Bidirectional changes in health behaviours associated with lockdown have also been reported in other contexts including alcohol use and vaping [ 9 , 21 , 22 ]. On this basis, it has been suggested that public health policies, measures and media are required to promote greater self-awareness, self-help, and self-care within the home setting to prevent later strains on the healthcare system [ 23 ].…”
Section: Discussionmentioning
confidence: 90%
“…These findings highlight the importance of continued public health messaging on smoking, especially as we emerge from the Covid-19 pandemic. Bidirectional changes in health behaviours associated with lockdown have also been reported in other contexts including alcohol use and vaping [ 9 , 21 , 22 ]. On this basis, it has been suggested that public health policies, measures and media are required to promote greater self-awareness, self-help, and self-care within the home setting to prevent later strains on the healthcare system [ 23 ].…”
Section: Discussionmentioning
confidence: 90%
“… 9 However, similar to our findings, another cross sectional online study from the United Kingdom (conducted in May-June 2020) found no difference in self-reported diagnosed/suspected COVID-19 between never, current and former e-cigarette users. 10 Compared with these previous investigations, our study analyzed a clinical cohort (ie, patient seeking medical care) and used self -reported e-cigarette use data that were confirmed and documented in an EHR by a clinician. 6 Also, COVID-19 diagnosis in our study was confirmed using a diagnostic PCR test.…”
Section: Discussionmentioning
confidence: 99%
“… 8 With regard to susceptibility to COVID-19 and severity of disease, the data remain conflicting. 9 - 12 An article published by Gaiha et al 13 in July 2020, concluded that COVID-19 was “five times more likely among ever users of c-cigarettes and 7 times more likely amongst dual users.” However, another study found that using e-cigarettes did not pose an increased risk for COVID-19. 14 There have been several letters and publications 15 , 16 which have been critical of the quality of data and analysis used by Gaiha et al 13 Aside from the content and potential harms of e-cigarettes, sharing of vaping devices has been raised as a potential concern for the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%